STRATEGI PENGEMBANGAN USAHA KECIL MENENGAH DIMASA PANDEMI COVID-19 - Ika Karimah; Lisa Iryani (Negotium: Jurnal Ilmu Administrasi Bisnis, 2022)
The purpose of this study is to analyze the development strategy of SMEs during the Covid-19 pandemic. The research method used is a qualitative  approach.  The results in this study are SME development strategies  during  the  covid-19  pandemic  in  Simpang  Ulim  District,  East  Aceh  Regency,  namely identifying  the SME environment, analyzing the SME environment internally  and externally  based on SWOT  analysis, formulating  the success measures  of the strategies  designed  based on the analysis. previously,  determine  goals  and targets, measurable,  and evaluate  various alternative  strategies  by considering the available resources and external conditions  faced and choosing the most appropriate strategy  to achieve  short-term  and long-term  goals. The obstacles  in the SME development  strategy during the COVID-19 pandemic in Simpang Ulim District, East Aceh Regency are marketing difficulties, financial  limitations,  limited Human Resources (HR) and raw material problems. It is hoped that the government will continue to pay attention to the SME sector so that it continues to grow, the development of SMEs in each region will show the level of success of leaders in advancing their region.